Model Kontrol Keimigrasian dalam Mencegah Tindak Pidana Terorisme di Indonesia - Citrawan, Harison; Nadilla, Sabrina (University of Jember, 2019)
This article attempts to elaborate an immigration control model that is capable in preventing terrorist activities in Indonesia. By observing several terrorism case-laws, this study draws a nexus between terrorism and several aspects within immigration, including passport issuance, border control, foreigner surveillance, and visa and entry permit issuance. Technically, in relation to such a nexus, this study finds that the current immigration control model is built upon three elements of duty: namely intelligence, surveillance, and border control. In principle, these three elements ought to be executed as an interconnected cycle. Consequently, a preventive control model should be circular, in the sense that any activities between elements of duty cannot be separated from one another. In order to become an established terrorism prevention mechanism, this control model requires information and data exchange amongst the immigration units. Moreover, any involvements from other institutions, such as police, BNPT, BIN, and NCB-Interpol are also preconditioned to ensure the efficacy of the circular model. Keywords: Immigration, Control, Terrorism